A metáfora na metaficção historiográfica: um “sonho de linguagem” em O outro pé da sereia, de Mia Couto - Coelho, Sofia Soares Alves (2019)
The purpose of this dissertation is to verify how the confluence of the literary historical discourse is processed, through metaphorical language, in the novel O outro pé da sereia, by Mia Couto, as well as to show in which specific dimension of the time-space of the reading of the novel, the metaphor transforms historical discourse into tension with fictional discourse. With regard to the official discourse of the Mozambican colonization and the historical novel exposing a brief trajectory of the construction of this type of novel, under the support of the theory of historiographic metafiction (Linda Huntcheon), we will focus on the fictional work, built from the historical discourse. The central axis is the metaphorical language of Mia Couto, that is, as the author alters the official discourse of Mozambican colonization through a unique writing made up of metaphors and poeticity, which also causes metaphorical effects in the contemporary setting of Mozambique. The authors used as reference are Maurice Lefevbe, Tezvetan Todorov, Roland Barthes, Edward Lopes, Donald Davidson, among others. From the analysis of the novel, the present work also aims to demonstrate how, always via language, the Coutian novel points to the reconstruction of the official discourse of the Mozambican colonization in order to present the history from the point of view of the colonized. We want to demonstrate that the appreciation of Mozambican culture and the poetic language of Mia Couto go hand in hand with the need for knowledge of Mozambican literature, as each country on the African continent has its own culture and identity